TRAFFIC PERFORMANCE ANALYSIS OF SECTIONS JL. PATI RAYA-JUWANA AT THE INTERSECTION OF ALUN-ALUN JUWANA PATI REGENCY USING THE MKJI 1997 METHOD - Hanafi, Irfan; Suwandi, Putri Anggi Permata; Yudaningrum, Farida (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2024)
The signaled interchange  at Jl. Pati  Raya-Juwana is one of the influential transportation infrastructure for road users who will go to Pati City, Rembang and the industrial center in Juwana. During rush hour the area often has traffic jams. Therefore,  this study was carried out with the aim of analyzing signaling intersections, replanning cycle times, knowing the traffic characteristics of the Pati Raya-Juwana road section.  Data collection was carried out for 4 days by taking peak hours at 06:30 WIB – 07:30 WIB and 16:00 WIB – 17:00 WIB. Themethod of data retrieval carried out is traffic flow, volume, and cycle time at traffic light. The results of the study were  pthere were existing conditions chosen alternative A as the best alternative for replanning traffic cycle time with 2 phases tonario 1 dwith t saturation degree 0.68, queue length 34.83 m and delay 15.06 seconds on the south shortening, then on the western approach for the saturation degree 0.51, queue length 23.51 m and delay of 11.07 seconds,  and 0.19 degrees of saturation, a queue length of 12.32 m, and a delay of 11.39 seconds on the north quarter. From the results of the analysis, it can be concluded that the results of the traffic performance evaluation at the Juwana square intersection obtained the highest volume on Monday, July 3, 2023, so it is recommended to reset the traffic cycle time.